Accuracy of the Minicardio system for heart rate variability analysis compared to ECG - Cassirame, J.; Stuckey, M. I.; Sheppard, F.; Tordi, N. (The Journal of Sports Medicine and Physical Fitness, 2013)
Aim: The purpose of this investigation was twofold: firstly, to assess the accuracy of heart rate (HR) measurements from Minicardio compared to a standard electrocardiogram (ECG) and secondly, to compare the heart rate variability analysis carried out for each set of data. Methods: Fifteen young participants volunteered for this study and were instrumented for the simultaneous recording of HR via ECG and Minicardio. HR was recorded continuously during 10 minutes of supine rest and 2 consecutive exercise bouts (target HR at 130 bpm and 150 bpm). R-R intervals were determined in order to compare the number and type of artifacts in each data set. The device were then compared by determining the type and number of artifacts, correlations between HRV analysis parameters and Bland-Altman limits of agreement. Results: No artifact was produced from ECG. With Minicardio, no artifact was produced during supine rest, during exercise there were 2 type 1 (long R-R interval) and 7 type 2 artifacts (short R-R interval). For time domain analysis, Pearson coefficients were 1 for SDNN and mean R-R interval and 0.99 for RMSSD and pNN50. For frequency domain analysis, Pearson coefficients were 0.99 for high frequency and low frequency power, and 0.99 for Poincaré plots SD1 and SD2. Limits of agreement from Bland-Altman analysis showed an excellent agreement between all devices Conclusion: The similarity between ECG and Minicardio encourages us to use Minicardio as a portable HR recorder for subjects at rest and during moderate cycling exercise.